2024
DOI: 10.3390/buildings14030841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precursor Blending Ratio and Rotation Speed of Mechanically Activated Fly Ash on Properties of Geopolymer Foam Concrete

Xuan Liu,
Tao Jiang,
Chenglong Li
et al.

Abstract: This research used fly ash and slag to create geopolymer foam concrete. They were activated with an alkali, resulting in a chemical reaction that produced a gel that strengthened the concrete’s structural integrity. The experimental approach involved varying the fly ash content in the precursors at incremental percentages (10%, 30%, 50%, 70% and 90%) and subjecting the fly ash to mechanical activation through a planetary ball mill at distinct rotational speeds (380, 400, 420 and 440 rpm). The investigation dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The bottles were washed and oven-dried before being manually crushed to yield particles <10 mm. These particles were further processed in a ball mill [11] (TS RUBENS, São Paulo, Brazil) at a speed of 100 rpm with steel grinding bodies (36.5; 30.2; 25.4; 19.1; 15.9 mm) until they were fine enough to pass through a 150 ABNT standard mesh sieve (106 μm). The milling time was not regulated.…”
Section: Glass Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…The bottles were washed and oven-dried before being manually crushed to yield particles <10 mm. These particles were further processed in a ball mill [11] (TS RUBENS, São Paulo, Brazil) at a speed of 100 rpm with steel grinding bodies (36.5; 30.2; 25.4; 19.1; 15.9 mm) until they were fine enough to pass through a 150 ABNT standard mesh sieve (106 μm). The milling time was not regulated.…”
Section: Glass Powdermentioning
confidence: 99%
“…This burden primarily arises from its high energy consumption, significant emissions that contribute to the greenhouse effect, and the generation of vast amounts of solid waste [9,10]. The global trend towards building taller structures has escalated concrete production, making it the most utilized material worldwide [11][12][13][14], with annual production nearing 10 billion cubic meters [15]. Research has indicated that construction processes can integrate various waste materials into concrete, such as vitreous foams [7,8], bamboo fibers [16], PET bottles [17], and glass bottles [18], to mitigate environmental impacts.…”
Section: Introductionmentioning
confidence: 99%